Effects of Teaching English-Writing Skills in a Flipped Classroom: An Analysis of ESL Teachers at Tertiary Level in Bangladesh - Nazmun, Mainul Islam (International Journal of Language and Literary Studies, 2025)
In this study, the flipped-classroom model has fostered a commitment to informative research, particularly within the domain of English as a Second Language (ESL) teaching at the tertiary level in Bangladesh. Upon shifting authentic, straight-coaching in the external university class and concentrating class time on supportive, learner-driven activities, this approach helps boost learners’ writing skills. The exploration of the efficiency of the flipped classroom in schooling writing to ESL learners who will be able to investigate remaining literature and realize the consequences as testified by ESL mentors. Building on a synthesis of prior investigations, this study examines the advanced level of compensation and contestation involved in implementing flipped classroom strategies in ESL writing instruction. It also explores the flipped-classroom model and the role of learners, which has a lasting impact on them, promoting self-sufficiency and inclusive writing performance while identifying potential obstacles to its success. The findings recommend that, whereas the flipped-classroom model has the potential to nurture learners’ empowerment and enhance writing skills at the tertiary level, its efficacy depends on appropriate implementation, learners’ engagement, and access to necessary technological equipment.